IMPLEMENTASI STRATEGI PEMBELAJARAN MODELLING THE WAY PADA MATA PELAJARAN FIKIH DI MADRASAH IBTIDAIYAH ROUDLOTUL MUBTADIIN WONOREJO PASURUAN - Makhrus Ali; M. Anang Sholikhudin (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
The mission of fikih study at Roudlotul Mubtadiin Islamic Elementary School Wonorejo Pasuruan is to help students recognize and know the basic components of Islamic law, and even the mechanisms for applying it into effect in everyday life. One of the problems that Roudlotul Mubtadiin Islamic Elementary School Wonorejo Pasuruan faces is pupils' poor knowledge and remembering. This situation is the consequence of an already learning process and the use of ineffective learning strategies. The research utilized a descriptive method with a case study approach as the research method. Observation, interviews, and documentation are used to mine data. Data reduction, data display, and data verification are all used to analyze research data. According to the research findings first, the implementation of modelling the way learning strategies in fikih subjects at Roudlotul Mubtadiin Islamic Elementary School Wonorejo Pasuruan can enhance the quality of fikih learning. This is referred to as active and excited student reactions to the fikih learning process, and also their excitement for engaging inside it. Second, the effect of learning strategies modelling the way on fikih subjects at Roudlotul Mubtadiin Islamic Elementary School Wonorejo Pasuruan can make students will become more focused, lessons will be easier to comprehend, and they will be able to compare content and practice.